3D Stack Integrated Triboelectric Nanogenerator for Harvesting Vibration Energy. (24th March 2014) - Yang, Weiqing; Chen, Jun; Jing, Qingshen; Yang, Jin; Wen, Xiaonan; Su, Yuanjie; Zhu, Guang; Bai, Peng; Wang, Zhong Lin
Abstract : The applications of a single‐layer triboelectric nanogenerator (TENG) may be challenged by its lower output current, and a possible solution is to use three‐dimensional (3D) integrated multilayered TENGs. However, the most important point is to synchronize the outputs of all the TENGs so that the instantaneous output power can be maximized. Here, a multi‐layered stacked TENG is reported as a cost‐effective, simple, and robust approach for harvesting ambient vibration energy. With superior synchronization, the 3D‐TENG produces a short‐circuit current as high as 1.14 mA, and an open‐circuit voltage up to 303 V with a remarkable peak power density of 104.6 W m −2 . As a direct power source, it is capable of simultaneously lighting up 20 spot lights (0.6 W ea.) as well as a white G16 globe light. Furthermore, compared with the state‐of‐the‐art vibration energy harvesters, the 3D‐TENG has an extremely wide working bandwidth up to 36 Hz in low frequency range. In addition, with specific dimensional design, the 3D‐TENG is successfully equipped inside a ball with a diameter of 3 inches, using which 32 commercial LEDs are simultaneously lighted up via hand shaking, exhibiting great potential of scavenging the abundant but wasted kinetic energy when people play basketball, football, baseball, and so on. Abstract : A 3D stack integrated TENG is rationally designed to harvest ambient vibration energy. With superior operation synchronization, the 3D‐TENG produces a remarkable peak power density of 104.6 Wm −2 . The capability of harvesting kinetic energy when people play various kinds of ball sports is demonstrated. And large amount of these self‐powered balls can also be woven into webs for ocean wave energy harvesting, which can be potentially applied to large‐scale energy generation.